Age and Sex Are Critical Factors in Ischemic Stroke Pathology - Roy-O’Reilly, Meaghan (Endocrinology, 2018)
Ischemic stroke is a devastating brain injury resulting in high mortality and substantial loss of function. Understanding the pathophysiology of ischemic stroke risk, mortality, and functional loss is critical to the development of new therapies. Age and sex have a complex and interactive effect on ischemic stroke risk and pathophysiology. Aging is the strongest nonmodifiable risk factor for ischemic stroke, and aged stroke patients have higher mortality and morbidity and poorer functional recovery than their young counterparts. Importantly, patient age modifies the influence of patient sex in ischemic stroke. Early in life, the burden of ischemic stroke is higher in men, but stroke becomes more common and debilitating for women in elderly populations. The profound effects of sex and age on clinical ischemic stroke are mirrored in the results of experimental in vivo and in vitro studies. Here, we review current knowledge on the influence of age and sex in the incidence, mortality, and functional outcome of ischemic stroke in clinical populations. We also discuss the experimental evidence for sex and age differences in stroke pathophysiology and how a better understanding of these biological variables can improve clinical care and enhance development of novel therapies.